Analisis Kandungan Timbal (Pb) pada Udang Putih (Penaeus merguiensis) di Perairan Muara Badak - Magfirah, Andi; Hariani, Nova; Sudrajat, Sudrajat (BIOPROSPEK: Jurnal Ilmiah Biologi, 2016)
Study on Analysis of Lead (Pb) Heavy Metal in White Shrimp (P. merguiensis) on the Muara Badak Estuary was conducted in May until July 2016. This aims to determine how much the concentration of lead (Pb) heavy metals in water, sediment and white shrimp (P. merguiensis) in the Muara Badak estuary. The method is using purposive sampling at 3 stations namely, near the pier and the residents, the transportation lines near of fishermen and the transit of oil tankers. During the research the temperatures ranging between 29.705 ° C 30.025 ° C shows the range was quite good for the aquatic biota growth, pH ranged from 7.135 to 7.425 which included in the category of normal pH, salinity ranged from 3.64 to 22.415 ‰ which showed freshwater, TDS ranged 13300-2320 mg/L which included in the range of high and exceed the quality standards set, and DO range from 7.16 to 7.61 which included in the category of normal. Levels of lead (Pb) heavy metals were measured using Atomic Absorption Spectrophotometry (AAS). The mean levels of lead (Pb) heavy metals in the water from Station 1 to Station 3 are 0.515, 0.273 and 0.216 mg/L which exceeds the quality standards specified by KMNLH no. 51 2004 was 0.008 mg/L, the average concentration of lead (Pb) heavy metals in sediment was 0.844, 0.758 and 0.835 mg/kg which is still safe because it is below the quality standard is 36 mg/kg and the average concentration of lead (Pb) heavy metals on white shrimp (P. merguiensis) is 0.534, 1.079 and 0.921 mg / kg which exceeded the quality standards set by BPOM RI in 2009 at 0.5 mg / kg.